The Palgrave Handbook of Child Mental Health
LII, 647 p.
Keywords: A landmark publication in the field, this state of the art reference work includes contributions from leading thinkers across a range of disciplines on topics including ADHD, autism, depression, eating disorders and trauma. It is an essential resource for all those involved or interested in child mental health.